ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVING PROPORTIONAL COMPARISON PROBLEMS - Tito, Alya Sa’diyah Azzahra Putri; Muhtadi, Dedi; Sukirwan, Sukirwan; Suhaya, Suhaya (Journal of Authentic Research on Mathematics Education (JARME), 2024)
This study aims to analyze the difficulties students face in solving problems related to proportional comparison. This study employs a case study method based on the errors made by students in solving problems related to proportional comparison. Four students were selected as a theoretical sample from a group of 34 seventh-grade students at the junior high school in Tasikmalaya. These students were chosen due to their complex levels of errors, which included procedural errors, incomplete solutions, and mistakes in determining mathematical formulas. The results of the study indicate that students experience difficulties in solving proportional comparison problems, including: (1) difficulty in understanding mathematical language, (2) difficulty in understanding word problems, (3) the influence of mathematics anxiety, and (4) differences in learning styles. Interviews and classroom observations revealed that factors such as less varied teaching methods, a lack of contextual practice, and low learning motivation contribute to the difficulties experienced by students. The discussion of the research results emphasizes the importance of more interactive and contextual teaching approaches to enhance students' understanding of the concept of proportional comparison. The implications of this study highlight the need for the development of more innovative teaching materials and the use of educational technology to help students overcome these difficulties.